Condom use among women of reproductive age (18–49 years) in Puerto Rico during the 2016 Zika virus outbreak: secondary analysis of data from a cross-sectional, population-based, cell-phone survey - Carrie K Shapiro-Mendoza; Margaret Christine Snead; Karen T Chang; Ruby A Serrano Rodriguez; Connie Bish; Sascha R Ellington (BMJ Open)
Objectives Zika virus (ZIKV) can be sexually transmitted, and ZIKV infection during pregnancy can cause birth defects. Contraception is a medical countermeasure to reduce unintended pregnancy and ZIKV-associated birth defects. We estimated the prevalence of condom use and associated factors among women at risk for unintended pregnancy in Puerto Rico during the 2016 ZIKV outbreak.Design Secondary analysis of a cross-sectional, population-based, cell-phone survey.Setting and participants Women, 18–49 years, living in Puerto Rico during July–November 2016. We limited our analytical sample (n=1840) to women at risk for unintended pregnancy, defined as those who were sexually active with a man in the last 3 months and did not report menopause, hysterectomy, current pregnancy or desiring pregnancy.Outcome measures We estimated the weighted prevalence of any condom use among women at risk for unintended pregnancy. We calculated crude and adjusted prevalence ratios (aPRs) to examine the association between condom use and ZIKV-related factors, stratified by use of more effective versus less effective or no contraception.Results Overall, 32.7% (95% CI: 30.2% to 35.1%) of women reported any condom use in the last 3 months. Among women using more effective contraception, condom use was higher for women who received ZIKV counselling (aPR: 1.61, 95% CI: 1.15 to 2.25) and those worried about having a child with a ZIKV-associated birth defect (aPR: 1.47, 95% CI: 1.03 to 2.10). Among women using less effective or no contraception, condom use was associated with being worried (aPR: 1.20, 95% CI: 1.01 to 1.43) compared with those not worried about ZIKV infection or with a previous known infection.Conclusions During the 2016 ZIKV outbreak, one in three women at risk for unintended pregnancy reported any condom use. Counselling to promote consistent and correct condom use may address concerns regarding ZIKV among women of reproductive age, which may differ by use of effective contraception.